Usos del archivo y políticas de la memoria: un análisis del proceso de “apertura” de los archivos militares en Argentina (2003-2015) - Cinthia Balé (Nuevo mundo - Mundos Nuevos, 2018)
This article aims to describe and analyze the “opening” process of the Military Archives in Argentina. We will consider three courses of action that were unfolded by the Ministry of Defense during the ‘kirchneristas’ governments (2003-2015). First the task performed by the “Equipos de Relevamiento y Análisis Documental” (Documentary Research and Analysis Teams) with the purpose of finding evidence that could be of use for criminal prosecution. Second, the archivist policy developed by the “Programa de Modernización de Archivos” (Archive Modernization Program), and third the treatment and dissemination of the documents known to the public as “Actas Secretas de la Dictadura” (“Secret proceedings of the dictatorship”). We expect to show how each course of action implied not only a dispute over the “property” of the Archives but also an overlapping of different uses, criteria and expectations for the documents at stake. Finally, we intend to indicate how these differentiated approaches to the Archives were influenced -and at the same time- helped building a dominant memory regarding Argentina’s recent past.